DESIGN CONCEPT OF ENVIRONMENTAL PARK WITH COMMUNITY APPROACH RT06/RW03 DEPOK JAYA URBAN VILLAGE - Alam, Bambang Perkasa; Hakim, Fajar Affanul; Yuliasari, Indah (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2025)
This community service activity involves a team from Indraprata PGRI University acting as a team of experts to overcome the problems faced by partners. The limited knowledge of partners in developing the concept of open space is an effort to restore the environmental park as an open space for residents of RT06/RW03, Depok Jaya urban Village. The purpose of this community service is to provide ideas and concepts for designing an environmental park based on the activities of the RT06/RW03 community of Depok Jaya Urban Village, Depok. The method used is qualitative with the support of direct interview data with residents and the head of the neighborhood association regarding the partner's desire to revitalize the environmental park space and the support of book data, previous thoughts, and research to overcome partner problems. The results of the analysis of the environmental park have limited dimensions and an elongated space structure so that they produce a linear layout for park activities. The park space prioritizes the activity space and social interaction of residents individually and in groups. The park space is located in a dense settlement and directly adjacent to the community road, it is used strategically to support the functionality of linear space circulation. The results of this service are that the environmental park space of RT06/RW03, Depok urban Village, Depok is designed to include a badminton sports area, a recreation area that supports elderly activities, and a children's play area.